Kiss & tell - Khorram, Adib (Dial Books, 2022)
On boy band Kiss & Tell's first major tour, lead singer Hunter Drake grapples with a painful breakup with his first boyfriend, his first rebound, and the stress of what it means to be queer in the public eye.